Kumāra Gandharva - Vājapeyī, Aśoka, 1941- (Ustāda Alāuddīna Ḵẖām Saṅgīta Akādemī ke lie, Rājakamala, 1982)
Contributed articles on the life and works of Kumāra Gandharva (Shivaputra Shidramayya Komkali), b. 1924, Indian musician; includes lyrics and musical notations to a selection of songs sung by him.